A meta‐analytic review of brief guided self‐help education for chronic pain. (10th May 2016) - Liegl, G.; Boeckle, M.; Leitner, A.; Pieh, C.
Abstract: Up to 30% of the population in Western countries suffer from chronic pain. The treatment of chronic pain causes medical and socioeconomic problems. Guided self‐help (GSH) might be an effective supplementary treatment, however, the size of this effect is unclear. This meta‐analysis quantifies the effect of GSH on chronic pain. A systematic literature search was conducted using PubMed, Cochrane, Psyndex, Psycinfo and Scopus. Studies that investigated GSH in chronic pain conditions (children and adults) were included. Disability, quality of life and pain severity were defined as main outcomes. We conducted random effects models to calculate standardized mean differences (SMDs). By applying mixed models and subgroup analyses, we examined the moderating effects of sample characteristics (age; pain region), GSH format (online; face‐to‐face contact) and study characteristics (study quality; control condition). We identified 16 eligible studies, including 739 subjects. Between‐group analyses resulted in a medium, but heterogeneous effect size for pain severity (SMD = 0.51; CI95 : 0.21, 0.81). After excluding two samples suggesting small study bias, the effect on pain severity was small but homogeneous (SMD = 0.34; CI95 : 0.13, 0.54). We found a small effect size for disability (SMD = 0.30; CI95 : 0.10, 0.50). The pooled effect size for quality of life did not reach significance (SMD = 0.24; CI95 : −0.07, 0.54). We conclude that GSH has a small but robust effect on pain severity and disability in chronic pain patients. This applies to various GSH formats and patient populations. It seems reasonable to integrate GSH into clinical practice as a supplemental treatment option. What does this review add?: The present meta‐analytic review found small but robust effects of guided self‐help interventions for the treatment of chronic pain.